Analisis Pengaruh Nilai Tukar Rupiah, Suku Bunga SBI, Inflasi Terhadap Jakarta Islamic Index - Harun Santosa; Ashari Mursito Wisnu (ITB AAS INDONESIA Surakarta, 2018)
This research was conducted to find out whether there was an influence of the rupiah exchange rate, SBI interest rate, inflation rate on the Jakarta Islamic Index. The study population was the Jakarta Islamic Index with a sample of the Jakarta Islamic Index data for the 2007-2017 period. The method of analysis is done using multiple linear regression. The analysis shows that the rupiah exchange rate and SBI interest rate have a significant effect on the Jakarta Islamic Index, while inflation has no significant effect on the Jakarta Islamic Index. Simultaneously the exchange rate, interest rate and inflation have a significant influence on the Jakarta Islamic Index.